Nutritional, textural and sensory properties of bread from wheat, millet and sorghum based composite flour - Ahmad, Aneeq; Bashir, Shahid; Saeed, Kanza; Haima, Hafiza; Amir, Rai Muhammad; Khalid, Waseem; Ahmad, Muhammad; Sabir, Amanullah; Khalid, Muhammad Zubair; Ahmad, Nazir; Mohamed Ahmed, Isam A.; Younis, Mahmoud (Italian Journal of Food Science, 2025)
This study aimed to develop a composite flour-prepared bread by partially replacing wheat flour (WF) with millet flour (MF) and sorghum flour (SF) at varying levels (0–40%). Five formulations were tested: T0 (100% WF), T1 (90% WF, 5% MF, and 5% SF), T2 (80% WF, 10% MF, and 10% SF), T3 (70% WF, 15% MF, and 15% SF), and T4 (60% WF, 20% MF, and 20% SF). In the first phase, proximate composition, mineral content, dietary fiber, and antioxidant properties of millet and sorghum were analyzed. Millet and sorghum had moisture con-tents of 11.52% and 11.35%, respectively; ash contents were 2.04% and 2.16%, respectively; protein levels were 10.81% and 9.35%, respectively; and fat contents were 3.86% and 4.63%, respectively. The grains were also rich in dietary fiber, with millet containing 11.52% insoluble and 2.04% soluble fiber, while sorghum had 11.35% insoluble and 2.16% soluble fiber. Mineral analysis showed that sorghum and millet contained respective con-tents of the following: potassium (119.35 and 90.44 mg/100 g), magnesium (385.96 and 292.76 mg/100 g), cal-cium (33.24 and 38.44 mg/100 g), zinc (4.86 and 3.84 mg/100 g), and iron (6.13 and 4.46 mg/100 g). Antioxidant activity, measured through 1,1- diphenyl-2-picrylhydrazyl (DPPH), ferric-reducing antioxidant power, and total phenolic compounds was slightly higher in sorghum. In the second phase, composite flour bread was assessed for its proximate composition, mineral, physical properties, texture, color, and sensory characteristics over a storage period of 0–7 days. Moisture content decreased across all treatments, with T0 showing the highest initial moisture (35.44%). Protein content was highest in T3 (10.07% initially), while fat content ranged from 2.69% in T0 to 6.67% in T3. The highest crude fiber content was observed in T3 (1.32%). This study revealed that potassium in sorghum- and millet-based bread ranged from 6.66 mg/100 g to 8.14 mg/100 g, calcium from 12.80 mg/100 g to 14.86 mg/100 g, magnesium from 4.18 mg/100 g to 6.86 mg/100 g, iron from 4.69 mg/100 g to 6.15 mg/100 g, and zinc from 1.19 mg/100 g to 1.65 mg/100 g over 7 days. Bread volume and specific volume decreased with increasing levels of MF and SF, with T4 having the lowest volume (176.95 cm³) and specific vol-ume (1.91 cm³/100 g). T0 had the softest texture with the lowest hardness (13.38 N) and highest cohesiveness (0.94 on day 0). The color measurements indicated that bread became darker with higher levels of MF and SF. Sensory evaluation revealed that T3, with 15% each of MF and SF, achieved the highest scores in appearance, color, flavor, aroma, texture, and the overall acceptability, making it the best formulation for producing com-posite flour bread.